Adverse drug reaction with midazolam use in Emergency Department - Nik Azlan Nik Muhamad; Ahmad Khaldun Ismail; Hilwani Kaharuddin; Miao, Ching Heng; Qamarul Ariffin S; Syazwani Azwa S; Nazurah MS (Fakulti Perubatan, UKM, 2016)
Midazolam is one of the most commonly used drugs for sedation in Emergency Department (ED). This was a retrospective study conducted on 380 patients from December 2012 to May 2014 in ED of Universiti Kebangsaan Malaysia Medical Centre (UKMMC). The objective was to elicit the frequency of side effects and correlation to various factors i.e. socio-demography, co-morbidities, age groups and underlying illnesses. Out of 380 patients, 35 patients experienced side effects (20 patients with midazolam alone, 15 patients with combination of drugs). The average age was 42 years and the average dose of midazolam was 3.5mg. The most common other drug combined was fentanyl. The overall complication rate for midazolam was 5.3%. The most common side effect recorded was excessive somnolence (1.6%). Other side effects included local skin reactions (1.1%), vomiting (0.8%), headache (0.8%) and hypotension (0.5%). There was no significant association between the socio-demographic factors and drugs combination with the side effects of midazolam on patients. It was concluded that midazolam was a safe drug due to absence of any life-threatening side effects. There are possibilities that most side effects recorded could be caused by other comfounding factors e.g. underlying injuries or disease and combination with other drugs.